Gotta catch'em all! Pokémon GO and physical activity among young adults: difference in differences study. (13th December 2016) - Howe, Katherine B; Suharlim, Christian; Ueda, Peter; Howe, Daniel; Kawachi, Ichiro; Rimm, Eric B
Abstract : Objective To estimate the effect of playing Pokémon GO on the number of steps taken daily up to six weeks after installation of the game. Design Cohort study using online survey data. Participants Survey participants of Amazon Mechanical Turk (n=1182) residing in the United States, aged 18 to 35 years and using iPhone 6 series smartphones. Main outcome measures Number of daily steps taken each of the four weeks before and six weeks after installation of Pokémon GO, automatically recorded in the "Health" application of the iPhone 6 series smartphones and reported by the participants. A difference in difference regression model was used to estimate the change in daily steps in players of Pokémon GO compared with non-players. Results 560 (47.4%) of the survey participants reported playing Pokémon GO and walked on average 4256 steps (SD 2697) each day in the four weeks before installation of the game. The difference in difference analysis showed that the daily average steps for Pokémon GO players during the first week of installation increased by 955 additional steps (95% confidence interval 697 to 1213), and then this increase gradually attenuated over the subsequent five weeks. By the sixth week after installation, the number of daily steps had gone back to pre-installation levels. No significant effect modification of Pokémon GO was found by sex, age, race group, bodyweight status, urbanity, or walkability of the area of residence. Conclusions Pokémon GO was associated with an increase in the daily number of steps after installation of the game. The association was, however, moderate and no longer observed after six weeks.